Using dollahites ABCD - XYZ resource management model of crisis or stress as a framework for understanding financial Well-being - Mokhtar, Nuradibah; Abd. Rahim @ Abd. Wahab, Husniyah; Sabri, Mohamad Fazli; Abu Talib, Mansor (Center for Promoting Ideas, 2015)
Financial well-being is a perception of an individual's financial situation. Mostly financial well-being is connected with personal resource management. However, hardly any investigation has been done under financial stress situation while managing resources. This reflects that, resource management and stress management have been investigated separately which bring a gap in both areas. In understanding financial well-being, there is a need to integrate resource management and stress theory. Therefore, a model that covers both resource management and stress theory will be used namely Dollahite's ABCD-XYZ Resource Management Model of Crisis or Stress. This paper studies some of the common predictor variables of financial well-being in resource management under stress circumstances through ABCD-XYZ Resources Management Model of Crisis or Stress. Hence, this may guide interested parties to integrate both areas in their field.